SCIENTIFIC SUPPORT OF THE MEDICAL SECTION OF THE STATE PROGRAM OF THE BELARUS REPUBLIC FOR THE OVERCOMING OF THE CHERNOBYL ACCIDENT CONSEQUENCES - A. V. Rozhko (Радиационная гигиена)
A twenty-five year health follow-up of the affected population has shown that a properly structured State strategy on overcoming the consequences of disaster allow to maintain stable levels of morbidity and mortality. An important achievement in the system of medical help to the affected population is the organization of dynamic follow-up, as well as creating State Register of people exposed to radiation as a result of the Chernobyl accident as a tool for solving scientific and practical problems. The results of scientific researches obtained in the SO “The Republican Research Centre for Radiation Medicine and Human Ecology” were the basis for one of the Council of Ministers Decree and two Decrees of the Ministry of Health. Significant changes have been made in the order of assigning the causation connection of disease (disability) and the accident at the Chernobyl nuclear power plant and objective criteria for the formation of high radiation risk groups.In a whole, the rate of oncological morbidity in the affected population remains at the average republican level, but for certain categories of the affected population, referred to groups of enhanced radiation risk, there has been detected the presence of excess morbidity of some forms of malignant neoplasms.